The relationship between nurse competence and patient satisfaction - Sulistiyowati, Nopi; Supratman, Supratman (Jurnal EduHealth, 2024)
Competence is a level of skill or performance that includes being able to make nursing plans, as well as client care with priority diagnoses, evaluating the actions that have been taken so that by mastering these competencies, the nurse will be able to do things including doing a task. Patient satisfaction can be obtained through service quality, which is the ability to deliver services as promised and accurately (reliability), intention to help customers and provide rapid assistance (responsiveness), understanding ability and courtesy of officers to instill faith and trust in their customers (assurance), care, specific attention to customers (empathy), and the appearance of physical facilities, tools, officers, and interactions items (tangibles). Objective: Determine the association between nursing competency and patient satisfaction. Method: This form of research is quantitative. This is an explanatory survey study that uses a cross-sectional approach. The sample size was 96 patients. This study used non-proportional random sampling. The instrument utilized was a questionnaire. Result: frequency distribution based on nurse competence was found to be mostly incompetent as many as 95 people (99%) and frequency distribution based on patient satisfaction was found that most patients had low satisfaction as many as 77 people (80.2%). The chi-square statistical test yielded a score of ρ = 0 043. Conclusion: There is a relationship between the application of the team method and the performance of executive nurses at Dr. Moewardi Regional General Hospital.